Solving disputes for regional cooperation and development in the South China Sea a Chinese perspective - Wu Shicun (Oxford, United Kingdom Chandos Publishing, 2013)
This book discusses the South China Sea dispute from a Chinese perspective with regards to history, law, international politics, the economy, diplomacy and military affairs. Not only does it detail China's official position on the sovereignty and maritime disputes in the South China Sea, but also provides analyses of the related factors influencing the origin and development of these disputes. It further assesses the complexity, internationalisation and long-term struggle over the South China Sea and China's efforts in dispute resolution. Solving Disputes for Regional Cooperation and Development aims to help readers better understand a Chinese perspective on the complexity of the South China Sea disputes, including competition over the sovereignty of the islets, islands regime and its impact on maritime delimitation, overlapping maritime claims, and how the adjacent states can cooperate for resource development in the South China Sea. Wu Shicun is President of the National Institute for the South China Sea Studies, a sole national-level think-tank in China specializing in South China Sea studies and a wellrespected expert in the field of the South China Sea Studies, Nanjing, China. Publisher's note.
Introduction -- China's sovereignty claims over the Nansha Islands: historical evidence -- China's sovereignty claims over the Nansha Islands: a legal perspective -- China's dispute with Vietnam over the Nansha Islands -- China's dispute with the Philippines over the Nansha Islands -- China's disputes with Malaysia and Brunei over the Nansha Islands -- Recent developments and regional cooperation in the South China Sea.
Includes bibliographical references (pages 169-193) and index.
Keywords: Law of the sea -- South China Sea Region; Dispute resolution (Law) -- Southeast Asia; South China Sea -- International status; China -- Foreign relations -- 1976- . -- Southeast Asia; Southeast Asia -- Foreign relations -- 1976- . -- China